Integrative assessment of sediment quality in lower basin affected by former mining in Brazil - Bonnail, Estefanía; Buruaem, Lucas M. [UNESP]; Morais, Lucas G. [UNESP]; Araujo, Giuliana S.; Abessa, Denis M. S. [UNESP]; Sarmiento, Aguasanta M.; Ángel Delvalls, T. (Springer Nature, 2018)
The Ribeira de Iguape River (Southeast Brazil) is metal contaminated by mining activities. Despite it has been cataloged as “in via of restoration” by the literature, this basin is still a sink of pollution in some segments of the fluvial system. This study aimed to assess the sediment quality in the lower part of the RIR basin. The employed approach was based on biological responses of the freshwater clam Corbicula fluminea after 7-day exposure bioassays using as the reference site the Perequê Ecological Park. Toxic responses (burial activity and lethality) and biochemical biomarkers (GST, GR, GPx, LPO, MTs, AChE and DNA damage) were evaluated and then integrated with metal bioavailability and chemical concentrations to address the sediment quality in the area through the weight-of-evidence approach. A multivariate analysis identified linkages between biological responses and contamination. Results pointed that, despite being below the benchmarks of the US Environmental Protection Agency, there is slight metal contamination in the lower part of the basin which induces oxidative stress in C. fluminea; other toxic responses were sometimes attributed to As and Cr bioaccumulation. The sediment quality values (TEL–PEL values in mg/kg) were calculated for the current study for As (0.63–1.31), Cr (3.5–11.05), Cs (1.0–1.17), Cu (6.32–7.32), Ni (6.78–7.46), Ti (42.0–215), V (1.77–8.00). By comparison with other international guidelines, the sediment quality of the lower basin of the Vale de Ribeira does not identify a significant environmental risk.
Keywords: Biomarkers; Corbicula fluminea; Mining contamination; Ribeira de Iguape River; Weight of evidence